Levels of genetic diversity vary dramatically between Blastocystis subtypes - Stensvold, C. Rune; Alfellani, Mohammed; Clark, C. Graham (Infection, genetics and evolution, 2012)
► We examined the intrasubtype diversity in Blastocystis ST3 and ST4 from primates. ► ST3 shows vast genetic variation as opposed to the almost clonal ST4. ► Homogeneity of ST4 indicates relatively recent colonisation of humans. ► Anthroponotic transmission appears most common despite some evidence of zoonotic transmission. ► MLST is a powerful tool for molecular epidemiological studies of Blastocystis. Blastocystis is a common single-celled parasite of humans and other animals comprising at least 13 genetically distinct small subunit ribosomal RNA lineages (subtypes (STs)). In this study we investigated intra-subtype genetic diversity and host specificity of two of the most common subtypes in humans, namely ST3 and ST4, by analysing and comparing over 400 complete and partial nuclear SSU-rDNAs and data from multilocus sequence typing (MLST) of the mitochondrion-like organelle (MLO) genome of 132 samples. Inferences from phylogenetic analyses of nuclear SSU-rDNA and concatenated MLST sequences were compatible. Human ST3 infections were restricted to one of four identified MLO clades except where exposure to non-human primates had occurred. This suggests relatively high host specificity within ST3, that human ST3 infections are caused predominantly by human-to-human transmission, and that human strains falling into other clades are almost certainly the result of zoonotic transmission. ST4 from humans belonged almost exclusively to one of two SSU-rDNA clades, and only five MLST sequence types were found among 50 ST4s belonging to Clade 1 (discriminatory index: 0.41) compared to 58 MLST sequence types among 81 ST3s (discriminatory index: 0.99). The remarkable differences in intra-subtype genetic variability suggest that ST4 has a more recent history of colonising humans than ST3. This is congruent with the apparently restricted geographical distribution of ST4 relative to ST3. The implications of this observation are unclear, however, and the population structure and distribution of ST4 should be subject to further scrutiny in view of the fact ST4 is being increasingly linked with intestinal disease.